PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DIBURSA EFEK INDONESIA PERIODE 2014-2015 - Silin, Silin; Purwanto, Nanang; Mustikowati, Rita Indah (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2018)
The purpose is to examine and explain the effect of managerial ownership, institutional ownership and dividend policy on the quality of earnings listed on the Indonesia Stock Exchange (IDX) in 2014-2015. The population of this study is the banking sector companies listed on the Indonesia Stock Exchange. Sampling uses a purposive judgment sampling method. From a population of 139 manufacturing companies, 15 manufacturing companies were obtained as samples with the observation method for 2 years (2014-2015). Analysis of the data used in this study is the classic assumption test and hypothesis test. The research method used in this research is quantitative descriptive method. While the analytical method used is multiple linear regression analysis. The results of this study indicate that the variables of managerial ownership, institutional ownership and dividend policy have a significant effect on the quality of profits both partially and simultaneously. Dividend policy variables have the most dominant influence on earnings quality.